Modern Caribbean politics - Payne, Anthony, ed. (Ian Randle Pub. KingstonJA, 1993)
Reviews political and economic developments in the Commonwealth Caribbean in the 1980s. Looks at the contradictions of liberal economics and electoral politics in Jamaica; the democratic progress in the Dominican Republic; the chaos and disorder in Haitian politics; and the odyssey of the revolution in Cuba. Examines the interaction of political and economic problems in Trinidad and Guyana, Grenada and the Eastern Caribbean, and Suriname and Puerto Rico. Considers the economic crisis of the region, the growth of the new offshore Caribbean, and the politics of U.S. intervention, militarization and security.